Prognostic Values of Hemoglobin and Red Blood Cell Distribution Width to Overall Survival in Non-Hodgkin Lymphoma - Trisnawati, Lidwina Tika; Hardianti, Mardiah Suci; Purwanto, Ibnu (Faculty of Medicine Universitas Gadjah Mada, 2023)
Background. After the Rituximab era, baseline International Prognostic Index (IPI) is not sufficient for the initial risk stratification of patients with Non-Hodgkin lymphoma (NHL). Low hemoglobin (Hb) levels and high red blood cell distribution width (RDW) baseline are known to be associated with poor outcomes and overall survival in malignancy. This study aimed to evaluate the prognostic value of Hb and RDW to overall survival in NHL patients who undergoing chemotherapy at Dr. Sardjito Hospital.Method. A retrospective cohort study in NHL from patients’ medical records diagnosed from 2014 to 2018 and undergoing chemotherapy at Dr. Sardjito Hospital. The prognostic influence of clinical factors including Hb and RDW on 3 years of overall survival were studied by using Kaplan-Meier curves and univariate Cox regression tests. To evaluate the independent prognostic relevance of basic characteristics data (age, gender, BMI, performance status, Ann Arbor stage, extranodal involvement), Hb, and RDW, multivariate Cox proportional hazards regression was applied. Results. From 292 NHL patients included, the median Hb was 12.7 g/dL and the median RDW was 14.2%. The mean survival time was 31.13 months, 38 patients (13%) died during the 3 years of follow-up. The most common causes of death were sepsis (68.4%) and 12 patients (4.1%) died within <30 days of chemotherapy. Based on Cox regression univariate analysis, patients with lower Hb levels (<10 gr/dL) had a 3-year overall survival lower than Hb>10 gr/dL (71% vs. 87%, CI 95%, p=0.014), with Hazard Ratio 2.49 (p=0.02). Patients with higher RDW>15.5 levels had lower overall survival than patients with RDW<15.5 levels (77.5% vs. 91.1%, CI 95%, p=0.002), and Hazard Ratio 2.78 (p=0.02). Based on multivariate analysis, performance status (OR=2.589, CI 95%, 1.225-5.471, p=0.013) and RDW (OR=2.292, CI 95%, 1.106-4.48, p=0.026) are independent predictor factors of 3-year overall survival.Conclusion. NHL patients with lower Hb and higher RDW levels have lower 3-year overall survival.